Evaluation of bi-directional causal association between depression and cardiovascular diseases: a Mendelian randomization study. Issue 9 (9th July 2022) - Li, Gloria Hoi-Yee; Cheung, Ching-Lung; Chung, Albert Kar-Kin; Cheung, Bernard Man-Yung; Wong, Ian Chi-Kei; Fok, Marcella Lei Yee; Au, Philip Chun-Ming; Sham, Pak-Chung
Abstract: Background: Depression and cardiovascular disease (CVD) are associated with each other but their relationship remains unclear. We aim to determine whether genetic predisposition to depression are causally linked to CVD [including coronary artery disease (CAD), myocardial infarction (MI), stroke and atrial fibrillation (AF)]. Methods: Using summary statistics from the largest genome-wide association studies (GWAS) or GWAS meta-analysis of depression (primary analysis: n = 500 199), broad depression (help-seeking behavior for problems with nerves, anxiety, tension or depression; secondary analysis: n = 322 580), CAD ( n = 184 305), MI ( n = 171 875), stroke ( n = 446 696) and AF ( n = 1 030 836), genetic correlation was tested between two depression phenotypes and CVD [MI, stroke and AF (not CAD as its correlation was previously confirmed)]. Causality was inferred between correlated traits by Mendelian Randomization analyses. Results: Both depression phenotypes were genetically correlated with MI (depression: rG = 0.169; p = 9.03 × 10 −9 ; broad depression: rG = 0.123; p = 1 × 10 −4 ) and AF (depression: rG = 0.112; p = 7.80 × 10 −6 ; broad depression: rG = 0.126; p = 3.62 × 10 −6 ). Genetically doubling the odds of depression was causally associated with increased risk of CAD (OR = 1.099; 95% CI 1.031–1.170; p = 0.004) and MI (OR = 1.146; 95% CI 1.070–1.228; p = 1.05 × 10 −4 ). Adjustment for blood lipid levels/smoking status attenuated the causality between depression and CAD/MI. Null causal association was observed for CVD on depression. A similar pattern of results was observed in the secondary analysis for broad depression. Conclusions: Genetic predisposition to depression may have positive causal roles on CAD/MI. Genetic susceptibility to self-awareness of mood problems may be a strong causal risk factor of CAD/MI. Blood lipid levels and smoking may potentially mediate the causal pathway. Prevention and early diagnosis of depression are important in the management of CAD/MI.